The Analysis of Organizational Learning and role of Knowledge Management Component to Improve its - Hamid Tajdar (Journal of Global Pharma Technology, 2017)
In this study, we have tried to identify those factors among key success factors of knowledge management that their implementation increases the organizational learning of staff. The method of study was so that firstly eight key factors of success of 1. IT 2 human resource 3. Support of top managers 4.Training of staff 5.Motivating staff 6.Sharing 7.Organizational culture 8. Team work, and organizational learning were considered as the dependent variables. Then, the relationship between dependent and independent variables was investigated. The subject of knowledge management in the University of this is a new subject and investigating the success factors can play an important role in organizational learning of its staff. The population of this research is staff of Zabol University that their total number was 400 and a sample size of 190 was selected based on Morgan table. Data were collected by a standard questionnaire with Cronbach's alpha of 0.920, and t-test and SPSS software were used to analyze the collected data. The results show that the key success factors of knowledge management have impact on staff organizational learning. At the end of study, some recommendations have been presented to enhance organizational learning level and successful implementation of knowledge management systems to managers of Zabol.Keywords: Knowledge management, Organizational culture, Success factors, Organizational learning.